Effects of Resistance Training on Oxidative Stress-Related Biomarkers in Metabolic Diseases: A Review - Poblete-Aro, C (Springer-Verlag Italia s.r.l., 2018)
Social and behavioral patterns of physical activity and diet have contributed to the increased incidence of obesity, due to high caloric intake associated to low physical activity. This metabolic impairment can give rise to the occurrence of oxidative stress, which is a key factor in pathogenesis of several metabolic diseases such as metabolic syndrome or type 2 diabetes mellitus (T2DM). Previous studies have reported reduced blood levels of oxidative stress biomarkers and related clinical parameters in obesity, T2DM and metabolic syndrome, following endurance exercise. However, similar studies about the effects of resistance exercise are still lacking. The aim of the present review was to present an update of available evidence about the relationship between resistance training, exercise and oxidative stress biomarkers. Therefore, this knowledge could provide the basis suggesting potential clinical benefits of resistance training as an adjunct therapy for obesity and other metabolic diseases. © 2017, Springer-Verlag Italia S.r.l.